Factors Influencing Health Practices Among Mothers with Children Aged 0–5 Years in the Working Area of Sirait Public Health Center, Nainggolan District, Samosir Regency - Dewi R. Bancin; Friska Megawati Sitorus; Sharfina Haslin; Muhammad Syafii (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Maternal and child health is an important indicator in assessing the degree of public health. The toddler period (0–5 years) is a critical period that determines the quality of life of children in the future. Samosir Regency still faces various challenges in maternal health practices, especially related to low exclusive breastfeeding coverage and posyandu visits. This study aims to analyze the factors that influence health practices among mothers with toddlers in the working area of the Sirait Community Health Center in Nainggolan District. This study is an analytical survey with a cross-sectional study design. This study was conducted in the working area of the Sirait Community Health Center in Nainggolan District, from August to September 2025. The study population consisted of all mothers with children aged 0-5 years. The study sample consisted of 120 pregnant women, as the sampling technique used was purposive sampling. Data analysis consisted of three stages, namely univariate analysis, bivariate analysis using chi-square, and multivariate analysis using multiple logistic regression with a significance level of 95% (a=0.05). The results showed that the level of mothers knowledge about the concept of health (p=0.001; Exp.B=28.842), mothers perceptions of health and disease (p=0.012; Exp.B=11.184), access to health services (p=0.003; Exp.B=0.409, 95% CI: 1.323-2.445) together influence health practices among mothers with children aged 0-5 years in the working area of the Sirait Community Health Center, Nainggolan District, Samosir Regency. It can be concluded that knowledge, perception, and access to health services play an important role in shaping the health practices of mothers with young children. It is recommended that the Community Health Center and the Health Office improve maternal and child health education, expand access to services, and strengthen communication between health workers and the community to encourage the implementation of innovative health practices at the family level. Keywords: Health Practices, Knowledge, Perception, Access